2021
DOI: 10.1590/1980-220x-reeusp-2020-0368
|View full text |Cite
|
Sign up to set email alerts
|

Religious coping and hope in chronic kidney disease: a randomized controlled trial

Abstract: Objective: To evaluate the effect of prayer on religious/spiritual coping and on the hope of patients with chronic kidney disease undergoing hemodialysis. Method: Randomized, controlled and blinded clinical trial, carried out in a dialysis unit, with a total of 62 patients undergoing hemodialysis – 31 participants in intervention group and 31 in the control group. Intercession prayer was applied three times, in alternate weeks, during hemodialysis sessions. Differences between groups in the outcome of the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(31 reference statements)
0
3
0
1
Order By: Relevance
“…Interestingly, in this study, for patients, there was a decrease in anxiety and psychological symptoms of stress over time as well as a tendency towards improvements in the social aspects of QoL. Regarding improvements in the aforementioned aspects and patients' ability to adapt, there are several factors that impact patient coping, such as patients' perception of their own disease 63 , beliefs, emotions and behaviours 63 , coping style 64 , religious coping 65 , and spirituality 66 . A previous study showed that lower psychological resilience, lower education and greater cognitive distortions are factors associated with depression and anxiety in patients with CKD 67 .…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, in this study, for patients, there was a decrease in anxiety and psychological symptoms of stress over time as well as a tendency towards improvements in the social aspects of QoL. Regarding improvements in the aforementioned aspects and patients' ability to adapt, there are several factors that impact patient coping, such as patients' perception of their own disease 63 , beliefs, emotions and behaviours 63 , coping style 64 , religious coping 65 , and spirituality 66 . A previous study showed that lower psychological resilience, lower education and greater cognitive distortions are factors associated with depression and anxiety in patients with CKD 67 .…”
Section: Discussionmentioning
confidence: 66%
“…In this context, spiritual interventions became increasingly important for HD patients [103]. Through religious practices, reading religious books, listening to spiritual music, and changing perspectives, spiritual therapy promotes optimism, hope, gratitude, contemplation, patience, raising awareness, and addressing problems through religious beliefs [91,95,99,104,105]. Further, Hosseini, Naseri-Salahshour [106] found that HD-related fear of death can be addressed through religious counseling.…”
Section: Spiritual Practicesmentioning
confidence: 99%
“…Notably, these benefits can be felt when there is some physical disorder (morbidity) that may compromise the feelings about life valorization. [18] Therefore, before the above observance, the present study aimed to analyze whether religious coping and suicidal ideation behave as a predictive model for suicide attempts.…”
Section: Introductionmentioning
confidence: 99%